Individual Behavior in Entrepreneurial Organizations: An Integrated Theoretical Framework - Wihartono Wihartono; Dr. Lukman Hakim; Dr. Jamrizal (UTSAHA: Journal of Entrepreneurship, 2026)
This study constructs an integrated theoretical framework to explain individual behavior within entrepreneurial organizations by synthesizing cognitive, motivational, reinforcement, and psychoanalytic perspectives. Through a systematic literature review, it examines how personality, cognitive capabilities, motivational orientations, and unconscious psychological structures interact with entrepreneurial environments to produce distinctive behavioral outcomes. The analysis indicates that entrepreneurial behavior arises from complex interactions across these psychological dimensions, rather than from isolated traits. The framework elucidates how cognitive processes underpin opportunity recognition, motivational hierarchies shape goal pursuit, reinforcement contingencies guide learning, and unconscious dynamics influence decision-making and resistance to change. By bridging classical organizational behavior theories with contemporary entrepreneurial contexts, this research provides deeper theoretical explanations for personality-performance relationships, cognitive drivers of innovation, and motivational impacts on venture success. The findings suggest that effective entrepreneurial leadership requires a multidimensional understanding of these psychological factors. This work contributes to entrepreneurship theory and offers practical implications for leadership, human resource management, and entrepreneurship education. Future research should empirically validate this framework across diverse entrepreneurial settings and stages of the venture lifecycle.